Konsumsi Kopi untuk Mencegah Penyakit Alzheimer - Bimo Husodo (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Coffee is one of the most consumed beverages in the world and most adults drink coffee every day. Coffee contains hundreds of bioactive compounds, including caffeine, chlorogenic acid, polyphenols, and small amounts of minerals and vitamins, which are known to have positive effects on brain health. Alzheimer's disease is a degenerative disease of the brain and the most common cause of dementia characterized by decreased memory, language, problem-solving, and other cognitive skills that affect a person's ability to perform daily activities. The purpose of this literature study is to determine the benefits of coffee consumption in preventing Alzheimer's disease. Method. This research is a literature study and library sources used involving 15 libraries from 1 national journal and 14 international journals. Result. Several studies have shown the preventive effects of coffee on Alzheimer's disease and cognitive decline through various mechanisms such as a role in lowering plasma Aβ levels, as well as an antioxidant that can reduce inflammation and protect against dementia. Conclusion. Coffee can have a protective effect on Alzheimer's disease and is safe to consume if it does not exceed the recommended dosage